First Report of Root-Knot Nematode, Meloidogyne incognita , Infecting Buckwheat, Fagopyrum esculentum , in State of São Paulo, Brazil - Ferreira, Rivanildo Junior; Silva, Edicleide Macedo da; Nascimento, Daniel Dalvan; Santos, Letícia Bernabé; Trigo, Vitor Alves; Nogueira, Gabriel Pereira; Vargas, Pablo Forlan; Harakava, Ricardo; Soares, Pedro Luiz Martins (Plant disease, 2023)
Buckwheat ( Moench) belongs to the Polygonaceae family and has been widely cultivated due to its high nutritional, nutraceutical, and medicinal properties. Brazil ranks seventh-largest producer, with 66,000 tons produced in 2018. Buckwheat is also valued for its adaptability as a cover crop, in grain fields of soybean ( (L.) Merr., maize ( L.), and sorghum ( (L.) Moench) (Görgen et al. 2016, Babu et al. 2018) especially in fields highly infested with plant-parasitic nematodes (PPN). PPN cause severe root damage, suppressing plant development and yield production. In October 2018, six samples of roots and soil were collected in symptomatic patches of buckwheat, in Guaíra SP (20° 19' 32"S 48° 13' 15.4"W). Samples were analyzed in the Nematology Laboratory (LabNema), UNESP, Jaboticabal, SP, BR. Plants presented symptoms of yellow leaves and galled and volume-reduced roots. sp. was found, comprising 6,320 eggs and second-stage juveniles (J2s) from 10 g of root and 1,628 J2s in 100 cm³ of soil. Adult morphological characteristics, isoenzyme phenotype of esterase, and molecular analysis were performed to identify the species. The perineal patterns presented high and trapezoidal dorsal arch (n=15), and the males showed a trapezoidal labial region, including a high head cap formed by a large round labial disc that is raised above the medial lips and centrally concave (n=15) (Eisenback and Hirscmann 1981). These characteristics are typical in (Kofoid and White, 1912) Chitwood, 1949 (Nascimento et al., 2020; Eisenback and Hirschmann 1981; Netscher and Taylor 1974). The enzymatic phenotype was performed with females (n=8), and the phenotype I1 was verified, described by Esbenshade and Triantaphyllou (1985) as typical for . To confirm the species DNA samples were extracted from individual females (n=6) and PCR with specific primers for ( -F 5'- GTGAGGATTCAGCTCCCCAG-3' and -R 5'-ACGAGGAA CATACTTCTCCGTCC-3') and (Treub) Chitwood 1949 (Fjav 5'-GGTGCGCGATTGAACTGAGC-3' and Rjav 5'-CAG GCCCTTCAGTGGAACTATAC-3') that amplify SCAR markers described by Meng et al. (2004) and Zijlstra et al. (2000), respectively, and specific primers for Yang & Eisenback 1983 that amplify rDNA-IGS2 region ( -F 5'-AACTTTTG TGAAAGTGCCGCTG-3' and -R 5'-TCAGTTCAGGCAGG ATCAACC-3') described by Long et al. (2006) were tested. A fragment of 955 pb DNA size was amplified in -F/R primer, which confirmed the identification (Meng et. al., 2004). The original population was used to execute pathogenicity test. In a greenhouse, single buckwheat seeds (cv. IPR 91 Baili) were sown in six 5L pots filled with autoclaved-soil and inoculated with 3,000 eggs and J2s per pot (n=6) and control (n=6). After 60 days, the nematodes were extracted from roots and the was confirmed. An average of 15,738 eggs and J2s were recovered, (reproductive factor = 5.24), which confirmed buckwheat as a host to . The inoculated plants showed symptoms as those observed in the field. No symptom or nematode was noted on the control. has been reported causing high damage to the in California (Gardner and Caswell-Chen 1994) plus several crops in Brazil (Nascimento et al., 2020). However, this is the first report of this nematode infecting buckwheat in Brazil. Given the importance of buckwheat in Brazil, with extensive use as forage, cover crop, and its nutritional properties, this report is essential to specific management measures are adopted to avoid further losses.